2013
DOI: 10.1210/jc.2012-2119
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Risk of Hearing Impairment in Adults: A Meta-Analysis

Abstract: Current meta-analysis suggests that the higher prevalence of hearing impairment in diabetic patients compared with nondiabetic patients was consistent regardless of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
169
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(192 citation statements)
references
References 29 publications
19
169
3
1
Order By: Relevance
“…The analysis also revealed that the discovery is likely to be independent of the effects of aging or noisy environments. Stratified analyses showed a stronger association of DM with hearing loss in studies of younger diabetic participants (mean age of participants ≤ 60 years) compared with studies of older participants (23) . Continuing with the evaluation of the meta-analysis, a large variation in the prevalence of hearing loss in diabetic patients can be observed, with values ranging from 30% (population aged 20-60) to 78.2% (population aged 18-75) (23) .…”
Section: Discussionmentioning
confidence: 89%
“…The analysis also revealed that the discovery is likely to be independent of the effects of aging or noisy environments. Stratified analyses showed a stronger association of DM with hearing loss in studies of younger diabetic participants (mean age of participants ≤ 60 years) compared with studies of older participants (23) . Continuing with the evaluation of the meta-analysis, a large variation in the prevalence of hearing loss in diabetic patients can be observed, with values ranging from 30% (population aged 20-60) to 78.2% (population aged 18-75) (23) .…”
Section: Discussionmentioning
confidence: 89%
“…Although hyperglycaemia in diabetes is thought to lead to microangiopathy of the cochlea, resulting in hearing impairment, the temporal association between diabetes and ARHL remains unclear [30]. When we used HbA 1c levels as an index of glycaemic exposure, we found that they were positively associated with the prevalence of hearing impairment (Table 1) [31].…”
Section: Risk or Preventive Factors For Sensory Impairmentsmentioning
confidence: 92%
“…This impact of increased intra-peritoneal fluid on pulmonary function has been demonstrated in several studies. For example, patients after ascites paracentesis show improvement in dyspnea through an increase in total lung capacity (TLC) and residual volume (RV) (4,5). It has been described that with the infusion of 2 L of dialysis fluid in the peritoneal space patients can feel dyspnea, which is most prominent in the sitting position…”
Section: Impact Of Peritoneal Dialysis On Pulmonary Function Test In mentioning
confidence: 99%